2006
DOI: 10.3141/1980-09
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Adaptive Cruise Control and Alert Modality on Driver Performance

Abstract: Adaptive cruise control (ACC) represents a rapidly emerging in-vehicle technology that has the potential to enhance driving safety. A critical factor governing the safety benefit of ACC concerns the ability of the driver to assume control of the vehicle in situations that exceed the capability of ACC. This study examined the effectiveness of various warning modalities in reengaging drivers who were likely to be distracted during severe braking situations that exceed the capability of ACC. The study compared wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…Llaneras (2006) indicates that ACC users think more highly of ACC when they are confident that the system can maintain safe headways, and perhaps the variable, willingness to repurchase, is picking up some of those perceptions. The connection between safety and trust has previously been suggested by Lee et al (2006) and Llaneras (2006), but the data available for this study do not provide as strong an evidence for this connection. That said it is a link that will have an impact on user acceptance and should be examined further.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Llaneras (2006) indicates that ACC users think more highly of ACC when they are confident that the system can maintain safe headways, and perhaps the variable, willingness to repurchase, is picking up some of those perceptions. The connection between safety and trust has previously been suggested by Lee et al (2006) and Llaneras (2006), but the data available for this study do not provide as strong an evidence for this connection. That said it is a link that will have an impact on user acceptance and should be examined further.…”
Section: Discussionmentioning
confidence: 52%
“…ACC achieves this by using forward radars and sensors to automatically modulate the acceleration and deceleration (Lee, McGehee, Brown, & Marshall, 2006). The original intent of ACC was for convenience rather than safety (Kesting, Treiber, Schönhof, & Helbing, 2007;Klunder, Li, & Minderhoud, 2009;Rudin-Brown & Parker, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have explored using auditory, visual and tactile feedback to help cognitively challenged individuals combat drowsiness and/or to prevent concentration lapses (Dingus et al, 1997;Belz et al, 1999;Liu, 2001;Ho and Spense, 2005;Lee et al, 2006;Spence and Driver, 1998;Spence and Ho, 2008;Lin et al, 2009). For example, Lin et al (2009) recently showed that the mean RT of lane-departure driving sessions with auditory feedback was 1.15 s shorter than those sessions that did not deliver any feedback to participants.…”
Section: Effects Of Auditory Feedback On Task Performancementioning
confidence: 95%
“…Dingus et al (1997) and Spence and Driver (1998) proposed using warning signals to maintain drivers' attention. The warning signals could be auditory (Spence and Ho, 2008;Lin et al, 2009), visual (Liu, 2001), tactile or mixed (Lee et al 2006). Belz et al (1999) compared the efficacy of these warning signals and showed that drivers were less sensitive to visual alarms since the driver needed to pay attention to road conditions and the dashboard.…”
Section: Introductionmentioning
confidence: 98%
“…Previous research indicate auditory warning signals to significantly improve driving by alerting the driver (Lin et al, 2009) and resulting in faster mean brake reaction times compared to visual warnings (Scott & Gray, 2008). Additionally, a number of studies found auditory and vibrotactile warning signals to improve a driver's reaction to possible front-to-rear-end collisions (Ho, Reed, & Spence, 2006;Ho & Spence, 2005;Ho, Tan, & Spence, 2006;Kiefer et al, 1999;Lee, Hoffman, & Hayes, 2004;Lee, McGehee, Brown, & Marshall, 2006;Suzuki & Jansson, 2003). In one of their earlier studies, Ho and Spence (2005) found warning systems that convey both symbolic and spatially predictive information is most suited for collision avoidance systems.…”
Section: Introductionmentioning
confidence: 93%